Perceived causes of cancer in a rural community of Ethiopia: a qualitative study - Abigiya Wondimagegnehu; Muluken Gizaw; Lidya Genene Abebe; Brhanu Teka; Andreas M. Kaufmann; Tamrat Abebe; Shannon A. McMahon; Adamu Addissie; Eva J. Kantelhardt (Taylor & Francis Group, 2024)
Background Although cancer incidence and mortality are rising in Ethiopia, lay and health professional perceptions of the disease remain limited. Objective To explore perceptions of cancer, including its causes, signs and symptoms, and transmission within a rural community in Ethiopia. Methods We conducted a qualitative study in four rural neighbourhoods of Butajira in central Ethiopia. Seven Focus Group Discussions (FGDs) and six In-Depth Interviews (IDIs) were held with community members, women representatives, religious leaders and key informants using two interview guides (divided by method). Behaviour change theories and a community research framework were used to summarize the findings. Results Across respondent categories and data collection methods, respondents described cancer or nekersa, which translates as 'an illness that cannot be cured', as serious and fatal. Cancer was further viewed as becoming more common and as underpinning more deaths particularly among women. Causes of cancer largely focused on individual behaviours namely mitch (referring to exposure to sunlight), poor personal hygiene and urinating on the ground/dirty areas. Almost all participants strongly related cancer to a wound that does not heal and entails a foul-smelling discharge. Bleeding and weight loss were other commonly mentioned complaints of cancer. Conclusions Although cancer is known among rural communities in this area, misconceptions about cancer aetiology and conflation of the signs and symptoms of cancer versus other diseases merit health messaging. Our study calls for design research to determine how to culturally tailor educational materials and deliver health campaigns regarding cancer causes, signs and symptoms within this context.